2016
DOI: 10.1002/jcp.25690
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte Progenitor Cells Directly Utilize Lactate for Promoting Cell Cycling and Differentiation

Abstract: Oligodendrocyte progenitor cells (OPCs) undergo marked morphological changes to become mature oligodendrocytes, but the metabolic resources for this process have not been fully elucidated. Although lactate, a metabolic derivative of glycogen, has been reported to be consumed in oligodendrocytes as a metabolite, and to ameliorate hypomyelination induced by low glucose conditions, it is not clear about the direct contribution of lactate to cell cycling and differentiation of OPCs, and the source of lactate for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 60 publications
(83 reference statements)
1
42
0
Order By: Relevance
“…Notably, OGD alters the gene expression profile in adult cultures only, increasing the expression level of genes involved in glycolysis, the regulation of glucose metabolism, the TCA cycle, PPP, glycogen synthesis, glycogen degradation, and glycogen metabolism. This gene expression regulation indicates that adult OPCs/astrocytes mixed cultures exposed to OGDs are able to regulate glycolysis, as was expected, but that they also fuel production from alternative substrates, such as glycogen, necessary for OPC survival and differentiation (Ichihara et al, ).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Notably, OGD alters the gene expression profile in adult cultures only, increasing the expression level of genes involved in glycolysis, the regulation of glucose metabolism, the TCA cycle, PPP, glycogen synthesis, glycogen degradation, and glycogen metabolism. This gene expression regulation indicates that adult OPCs/astrocytes mixed cultures exposed to OGDs are able to regulate glycolysis, as was expected, but that they also fuel production from alternative substrates, such as glycogen, necessary for OPC survival and differentiation (Ichihara et al, ).…”
Section: Discussionmentioning
confidence: 53%
“…OGDs are able to regulate glycolysis, as was expected, but that they also fuel production from alternative substrates, such as glycogen, necessary for OPC survival and differentiation (Ichihara et al, 2017).…”
Section: Discussionmentioning
confidence: 66%
“…Glycogen is highly enriched in white matter such as the corpus callosum where astrocyte density is high . Meanwhile, studies on glycogen phosphorylase inhibitor—DAB showed that, by inhibiting the hydrolysis of glycogen, DAB suppresses lactate release and worsens the outcome in myelin remodeling . Therefore, the role of lactate in response to metabolic demand is critical.…”
Section: Discussionmentioning
confidence: 99%
“…Our lab, and others, have previously reported higher expression of MCT1 in the CNS myelin than in axons and conversely higher expression of MCT2 in axons than myelin (Rinholm et al, 2011) (Lee et al, 2012). Recent studies have also identified that oligodendrocyte progenitor cells (OPCs) utilize lactate through MCTs and that lactate, produced from glycogen, is crucial to promote cell cycling and differentiation in OPC-rich culture (Ichihara et al, 2017). Surprisingly, an in vitro study using co-cultures of DRG neurons and Schwann cells demonstrated increased myelination following downregulation of MCT1 in Schwann cells by lentiviral shRNAs (Domenech-Estevez et al, 2015); thus the exact role of this transporter in SC myelination in not yet clear.…”
Section: Monocarboxylate Transportersmentioning
confidence: 99%